Crying over food: an extraordinary response to a multisensory eating experience - Rottigni, F; Spence, C (Elsevier, 2024)
Recent years have seen a growing awareness of the extraordinary responses that can sometimes be elicited in diners by food. One such response is crying, and it was this unusual behaviour that chef Federico Rottigni anecdotally observed in response to one of the dishes on his recently-introduced Ayuhuasca menu. In particular, something about Serendipity, the seventh course on a nine-course tasting menu currently served at the restaurant in Milan makes some diners want to cry. This is the first of three dessert courses, and consists of a small bowl of rice pudding covered with white wafers which are broken onto the dish in front of diners at the point of service. But why do a number of the diners spontaneously break into tears during this course? Several factors that may be contributing to this extraordinary emotional response are outlined. Importantly, rice pudding can be considered a nostalgic comfort food associated with childhood for many people. The dessert is accompanied by a complex multi-element soundscape consisting of a school bell, the voice of a female school teacher talking in Italian; Later in the recording, a spatially discrete voice of an old woman reminiscing in English is also heard; At the same time, a simple, almost hypnotic, ascending and descending musical riff is played repetitively, while a music track with sustained low frequency notes appears to help draw people's attention to their own body (bodily sensations). Together, and possibly synergistically (superadditively), these various multisensory elements, both on and off the plate, contribute to delivering what can be classed as an extraordinary multisensory gestalt dining experience for a number of the guests.